The Effects of Imagery on Muscle Performance and Pain Perception Associated with Delayed-Onset Muscle Soreness - Kensrue, Paige; Bixby, Walter R; Miller, Paul C; Hall, Eric E (Journal of Sports Research, 2016)
Research has indicated that imagery may aid in recovery from injuries and reduce the perception of pain in athletes during and after competitions. There is little research concerning acute pain and soreness, such as delayed-onset muscle soreness (DOMS). The purpose of this investigation was to determine whether the use of guided imagery for healing will affect soreness, pressure pain threshold (PPT), and muscle performance associated with DOMS. It was hypothesized that those who listened to a healing imagery script following inducement of DOMS would report less soreness, higher pain threshold, and have better muscle performance than a control group. Participants (thirty-eight) completed two days of testing with 48 hours between them. At the end of the first day, DOMS was induced by performing 6 sets of 15 reps of isokinetic eccentric exercise at -1.05 rad/sec. 20 participants listened to a healing imagery script 10 times within the 48 hours after inducement of DOMS while 18 listened to relaxing music. Each day consisted of tests of soreness, PPT, vertical jump, and a Wingate test. Healing imagery had no significant impact on perception of soreness, PPT, or vertical jump. The healing imagery group performed significantly better than the control group on the Wingate test in minimum power and power drop results following DOMS. Thus, it appears that imagery could impact long duration anaerobic performance as opposed to short duration explosive performance. Further research is needed to determine if healing imagery can improve performance on longer anaerobic and possibly aerobic activities. Additionally, it is possible that the limited exposure to the imagery in this investigation limited its ability to impact muscle performance and pain perception.